Роль стереотипів у формуванні етнічної самосвідомості - Чубарко, Вікторія Василівна; Чубарко, Виктория Васильевна; Chubarko, Viktoriia V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті здійснено теоретичний аналіз впливу стереотипів на формування етнічної самосвідомості, а також процесу формування й функціонування стереотипів у свідомості етнічних спільнот. Зокрема, основну увагу приділено обґрунтуванню поняття стереотипу, дослідженню особливості етнічних стереотипів та їхніх функцій, виокремлено основні різновиди етностереотипів українців, а саме: автостереотипи й гетереостереотипи (на прикладі ставлення українців Волинського регіону до росіян). The article analyzes the concept of stereotype, based on cognitive, psychological, historical approaches and theories that emphasize individual personality traits. It shows ethnic stereotypes as a kind of stereotype. The research on Ukrainian ethnic stereotypes, as factors shaping ethnic identity, is based on the attitude of Volyn region Ukrainians to Russians. It is focused on the core functions of ethnic stereotypes modern society as mechanisms regulating interethnic relations, namely, communicative, cognitive, protective and heuristic. The main empirical focus is on the function of strengthening and protection of positive ethnic identity, which provides education of tribal ethno-cultural values. In particular, according to the Institute of Sociology of National Science Academy of Ukraine, it was found that social distances reduce mostly among representatives of Eastern ethnic groups living at this area.
The Role of Stereotypes in Shaping Ethnic Identity
Keywords: стереотип; стереотипізація етнічний стереотип; стигматизація; етнічна самосвідомість; stereotype; stereotyping of ethnic stereotypes; stigmatization; ethnic identity